The Influence of Guided Inquiry Student Worksheet on Learning Outcomes and Science Process Skill on the Static Fluid Topic - Falamy, Ryna Aulia; Suyatna, Agus; Wahyudi, Ismu (Omega: Jurnal Fisika dan Pendidikan Fisika, 2017)
The purpose of this research is to know the influence of guided inquiry student worksheet on learning outcomes and describe learning outcomes and science process skill after using guided inquiry student worksheet. This research method was true experiment, with a sample grade of VIII H as a control class and VIII J as an experimental class, determined by purposive sampling technique. The study design used pretest-postest control group design. The data had been tested by using N-gain analysis, normality test, homogeneity test, and independent t-test. The results showed a significant effect of the use of guided inquiry student worksheet to the results of student learning outcomes. The average learning outcomes in cognitive domain of 85.24 and the improved learning outcomes with N-gain 0.81.